Sports and health physical education issues in online learning during the covid-19 pandemic in madrasah ibtidaiyah 5 north Lampung - Santoso, Nurhadi; Dwi cahyo, Anggoro; Wiyanto, Agus (Universitas Nusantara PGRI Kediri, 2021)
In some countries, the Covid-19 pandemic has become a disaster that causes serious problems, including in the field of Education. This research aims to find out the problem of physical education learning in online learning in the era of the Covid-19 pandemic. This research uses qualitative methods. The research subject is upper-class students from MIN 5 North Lampung school year 2020/2021, as much 106. The instruments the authors use are designed based on previous literature. Interview data is analyzed using content analysis. In most physical education activities interviewed by PJOK MIN 5 North Lamupung education teachers, the total sample of research used in the study was 111 subjects, taking subjects using total sampling techniques. The findings revealed physical education learning problems in PJOK online learning during the Covid-19 pandemic: online learning problems in teachers, limited innovation in online learning, teacher control during PJOK online learning, task problems in students. While the problem in students found difficult to access in online learning, students' interest is lacking in online learning PJOK, limited devices in accessing online learning, facilities, and infrastructure that do not support PJOK.